If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7k + -37 = 7(2k + -3) + k Reorder the terms: -37 + 7k = 7(2k + -3) + k Reorder the terms: -37 + 7k = 7(-3 + 2k) + k -37 + 7k = (-3 * 7 + 2k * 7) + k -37 + 7k = (-21 + 14k) + k Combine like terms: 14k + k = 15k -37 + 7k = -21 + 15k Solving -37 + 7k = -21 + 15k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-15k' to each side of the equation. -37 + 7k + -15k = -21 + 15k + -15k Combine like terms: 7k + -15k = -8k -37 + -8k = -21 + 15k + -15k Combine like terms: 15k + -15k = 0 -37 + -8k = -21 + 0 -37 + -8k = -21 Add '37' to each side of the equation. -37 + 37 + -8k = -21 + 37 Combine like terms: -37 + 37 = 0 0 + -8k = -21 + 37 -8k = -21 + 37 Combine like terms: -21 + 37 = 16 -8k = 16 Divide each side by '-8'. k = -2 Simplifying k = -2
| -3t-6=36 | | ((2x+1)/(x^4))((9x^4)/(6x+3)) | | 7x+6-3x-10=4 | | 2-(2x)/5=6 | | E+64=311 | | t/7--16=20 | | 80-5x=4x+10 | | C-75=4 | | 8+(x+2y)i=x+4i | | 7-3r=-5 | | B/25=400 | | 4x-3y=11/2 | | 2b-32=46 | | 10u-11=6z+13 | | 14A=42 | | 2x+60=4x-30 | | 10u-11=4z+13 | | T+94=944 | | 26(4x-11)=-5(x-7) | | x/2+6=3x-9+x/2 | | Z-45=3 | | -x+6y=-4 | | q/3-1=1 | | -5+15=10 | | N/9=130 | | 6-3f=-12 | | 0.5c-5=-18 | | 4x-3=x-59 | | 0.5-5=-18 | | Z+4=71 | | 44=-4(x-5) | | (B-1)=-6b+48 |